2017
DOI: 10.1002/lary.26625
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of corticosteroids for pain after transoral robotic surgery

Abstract: 1b. Laryngoscope, 127:2558-2564, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…We suspect this is due to their use of multimodal analgesia, including steroids . Steroids have been reported to reduce VAS pain scores and length of stay . Slama et al also investigated TORS for oral cancer and reported an average VAS of 5.1 for week 1, similar to our findings .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We suspect this is due to their use of multimodal analgesia, including steroids . Steroids have been reported to reduce VAS pain scores and length of stay . Slama et al also investigated TORS for oral cancer and reported an average VAS of 5.1 for week 1, similar to our findings .…”
Section: Discussionsupporting
confidence: 86%
“…13 Steroids have been reported to reduce VAS pain scores and length of stay. 14 Slama et al also investigated TORS for oral cancer and reported an average VAS of 5.1 for week 1, similar to our findings. 15 Thiels et al reported a median prescription of 350 MME and use of 180 MME in TORS tonsillectomies (49% unused) compared to our mean prescription of 368 MME and use of 221 MME (40% unused).…”
Section: Predictors Of Opioid Usesupporting
confidence: 90%
“…A 2013 systematic review of pain control strategies for HNC pain found that there was insufficient evidence from randomized controlled studies to suggest the optimal pharmacological intervention 31 . Since the time of that publication, randomized controlled trials have been published examining the efficacy of gabapentin, 32 celcoxib, 33 and corticosteroids 34 as adjuncts for pain control. These studies demonstrated no significant efficacy in reducing pain related to oral mucositis with gabapentin 32 or celcoxib 33 but did demonstrate some improvement with postoperative pain after transoral robotic surgery with corticosteroid 34 administration.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] In the present study, patients receiving dexamethasone also reported less pain and needed less oxycodone for 5 postoperative days. A study by Clayburgh et al 28 showed that extended perioperative corticosteroid use after transoral robotic surgery for initial treatment of oropharyngeal squamous cell carcinoma decreased the length of hospital stay, although postoperative pain was minimally affected. The present trial is the first prospective randomized study to evaluate the perioperative use of dexamethasone in patients with head and neck cancer and microvascular reconstruction.…”
Section: Discussionmentioning
confidence: 99%